Implementasi Pendidikan Berbasis Permainan Tradisional dalam Membentuk Karakter Anak di Sekolah Dasar - E. Anatasya; T. Rafifah; T. Rustini; Y. Wahyuningsih (Journal on Education, 2023)
Abstract At this time, children tend to enjoy playing with gadgets rather than playing with their friends. This has a negative impact, one of which is online games that affect togetherness with friends to carry out an activity, one of which is playing traditional games. The purpose of this study is to implement traditional game-based education in character building in elementary schools and also to increase the sense of nationalism with traditional games. Therefore, it is hoped that this paper can help awaken and educate readers of traditional games that can be implemented into learning.